Effect of die geometry on foaming behaviors of high-melt-strength polypropylene with CO2 - Lee P.C. (2014)
This article reports on a systematic study that was conducted to investigate the effects of die geometry (i.e., pressure and pressure. drop rate) on the cell nucleation and growth behaviors of noncrosslinked highmelt-strength (HMS) polypropylene (PP) foams blown with supercritical CO2. The experimental results showed that the cellular morphologies of PP foams were sensitive to the die geometry. Furthermore, the initial expansion behavior of the foam extrudate at the die exit was recorded using a high-speed CCD camera. This enabled us to achieve a more thorough understanding of the effect of die geometry on both the initial expansion behavior and the final cellular morphology of HMS PP foams. The effect of die temperature on cell morphology was also studied. © 2008 Wiley Periodicals, Inc.